Competitive enzymatic reaction to control allele-specific extensions - Hultin, Emilie (Oxford University Press, 2005)
Here, we present a novel method for SNP genotyping based on protease-mediated allele-specific primer extension (PrASE), where the two allele-specific extension primers only differ in their 3′-positions. As reported previously [Ahmadian,A., Gharizadeh,B., O'Meara,D., Odeberg,J. and Lundeberg,J. (2001), Nucleic Acids Res., 29, e121], the kinetics of perfectly matched primer extension is faster than mismatched primer extension. In this study, we have utilized this difference in kinetics by adding protease, a protein-degrading enzyme, to discriminate between the extension reactions. The competition between the polymerase activity and the enzymatic degradation yields extension of the perfectly matched primer, while the slower extension of mismatched primer is eliminated. To allow multiplex and simultaneous detection of the investigated single nucleotide polymorphisms (SNPs), each extension primer was given a unique signature tag sequence on its 5′ end, complementary to a tag on a generic array. A multiplex nested PCR with 13 SNPs was performed in a total of 36 individuals and their alleles were scored. To demonstrate the improvements in scoring SNPs by PrASE, we also genotyped the individuals without inclusion of protease in the extension. We conclude that the developed assay is highly allele-specific, with excellent multiplex SNP capabilities.